2021
DOI: 10.3390/min11010059
|View full text |Cite
|
Sign up to set email alerts
|

Flotation Behavior and Synergistic Mechanism of Benzohydroxamic Acid and Sodium Butyl-Xanthate as Combined Collectors for Malachite Beneficiation

Abstract: Sulfuration flotation is the most widely used technology in malachite beneficiation. However, the inhomogeneity of malachite surfaces usually results in a non-uniform sulfuration surface. The motivation of this work is attempt to adopt different functional combination collectors to enhance the sulfuration flotation of malachite. Accordingly, the flotation behaviors and adsorption mechanisms of benzohydroxamic acid (BHA) and sodium butyl-xanthate (SBX) on the surface of malachite were systematically investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Several studies have found that the combination of collectors can improve both the collecting ability and selectivity of reagents by leveraging the advantages of different collectors [12,78,79].…”
Section: Combined Collectorsmentioning
confidence: 99%
“…Several studies have found that the combination of collectors can improve both the collecting ability and selectivity of reagents by leveraging the advantages of different collectors [12,78,79].…”
Section: Combined Collectorsmentioning
confidence: 99%
“…Secondly, the synergist improves the solubility and dispersion of the collector in water by reducing the surface tension of the water, thus enhancing the efficiency of the collector. In addition, the synergist may form new compounds with the collector, changing the way the collector acts [19,20]. Due to improving the performance of fatty acid collectors, synergists are widely used in the flotation of low-grade oxidized ores.…”
Section: Introductionmentioning
confidence: 99%
“…BHA is known for its ability to form strong chelates with metal ions (Adiguzel et al, 2017, Kozlov et al, 2013, Schraml, 2000. It has been evaluated as collector in froth flotation of wolframite (Liu et al, 2019, Yang et al, 2014, monazite and dolomite (Espiritu et al, 2018), cassiterite (Cao et al, 2020, ilmenite (Fang et al, 2018, smithsonite (Wang et al, 2017), malachite (Zhang et al, 2021), rutile (Cao et al, 2019), muscovite mica (He et al, 2018), scheelite (Han et al, 2017, Wei et al, 2020, and rhodochrosite (Cui et al, 2023) minerals, as well as including pyrochlore-bearing (Gibson et al, 2017, Gibson et al, 2015 and rare earth (Jordens et al, 2016) ores. The adsorption mechanism of hydroxamic acids on the mineral surfaces, which involves a combination of chemical and physical interactions, can vary depending on the type of mineral and frother, pH, temperature, and presence of other chemicals, such as metal cations in the flotation system (Khalil and Fazary, 2004, Pavez and Peres, 1993.…”
Section: Introductionmentioning
confidence: 99%